2022
DOI: 10.3390/ijms23063393
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis Reveals Enzymes for β-D-Glucan Formation and Degradation in Levilactobacillus brevis TMW 1.2112

Abstract: Bacterial exopolysaccharide (EPS) formation is crucial for biofilm formation, for protection against environmental factors, or as storage compounds. EPSs produced by lactic acid bacteria (LAB) are appropriate for applications in food fermentation or the pharmaceutical industry, yet the dynamics of formation and degradation thereof are poorly described. This study focuses on carbohydrate active enzymes, including glycosyl transferases (GT) and glycoside hydrolases (GH), and their roles in the formation and pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…Furthermore, in our previous study, we showed that the decrease in viscosity of L. brevis TMW 1.2112 culture broth could not be explained by the degradation of late expressed enzymes including BglB. However, the viscosity decrease indicated the degradation of high-molecular β-glucan which may have been caused by so far unknown enzymes of this strain (Bockwoldt et al 2022 ).
Fig.
…”
Section: Resultsmentioning
confidence: 76%
“…Furthermore, in our previous study, we showed that the decrease in viscosity of L. brevis TMW 1.2112 culture broth could not be explained by the degradation of late expressed enzymes including BglB. However, the viscosity decrease indicated the degradation of high-molecular β-glucan which may have been caused by so far unknown enzymes of this strain (Bockwoldt et al 2022 ).
Fig.
…”
Section: Resultsmentioning
confidence: 76%